Tahap (reluctance) intersectionality of gender and indigeneity politics among the Bukidnon women in Negros - Mijares, Aileen May P. (2017)
This article draws on ethnographic research and discusses the intersections of gender and indigeneity politics in Don Salvador Benedicto (DSB), a municipality in Northern Negros Occidental, and examines women's subjectivities in matters pertaining to indigeneity and their views on their own positions in the community and gender norms. The article discusses the intra-group politics and addresses contestations over representation and authority and differing perspectives on development and argues for the importance of looking at the intersectionality of gender, indigeneity and development concerns. The article uses local term tahap (reluctance) as a conceptual frame in explaining women's subjectivity in relation to indigeneity politics.
Keywords: Identity politics